2017
DOI: 10.3389/fpls.2017.02208
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Cotton Leaf Curl Multan Betasatellite by Tomato Leaf Curl New Delhi Virus—Analysis by Mutation

Abstract: Viruses of the genus Begomovirus (family Geminiviridae) are economically important phytopathogens that are transmitted plant-to-plant by the whitefly Bemisia tabaci. Most Old World (OW) begomoviruses are monopartite and many of these interact with symptoms and host range determining betasatellites. Tomato leaf curl New Delhi virus (ToLCNDV) is one of only a few OW begomoviruses with a bipartite genome (components known as DNA A and DNA B). Four genes [AV2, coat protein (CP), transcriptional-activator protein (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 108 publications
1
16
0
Order By: Relevance
“…This feature hinders trying to address the identification of deltasatellite motifs/sequences involved in the interaction with their helper viruses and pathogenesis. Anyhow, mutation studies similar to those successfully performed with betasatellites [ 54 , 55 ] could help to decipher how deltasatellites are able to be transreplicated by different helper geminivirids and whether any of the hypotheses proposed for betasatellite-begomovirus recognition, the “universal Rep” hypothesis or the “universal iteron” hypothesis” [ 56 ], could also be applied to these small non-coding DNA molecules.…”
Section: Discussionmentioning
confidence: 99%
“…This feature hinders trying to address the identification of deltasatellite motifs/sequences involved in the interaction with their helper viruses and pathogenesis. Anyhow, mutation studies similar to those successfully performed with betasatellites [ 54 , 55 ] could help to decipher how deltasatellites are able to be transreplicated by different helper geminivirids and whether any of the hypotheses proposed for betasatellite-begomovirus recognition, the “universal Rep” hypothesis or the “universal iteron” hypothesis” [ 56 ], could also be applied to these small non-coding DNA molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly the efficient spread (infectivity) of the DNA A component in the presence of the betasatellite supports this. Betasatellites have previously been shown to complement DNA B functions suggesting that the only protein encoded by betasatellites, βC1, has movement functions 5052 . However, the demonstration that βC1has suppressor of both post-transcriptional and transcriptional gene silencing 17 may indicate that rather than providing movement functions, betasatellites instead overcome a host resistance to movement based on gene silencing.…”
Section: Discussionmentioning
confidence: 99%
“…However, the likely effects and stability of the TYLCV/ToLCB-MYMIV interaction are less clear. Previous studies of the interaction of bipartite begomoviruses with betasatellites has suggested that these might not be stable, either because of a conflict between the betasatellite and the DNA B 51 or due to a conflict between the virus encoded coat protein and the betasatellite 52 . Whether the TYLCV/ToLCB-MYMIV co-infection will prove to be stable in the field is unclear, although the low levels of MYMIV components detected in tomato in the field and by agroinoculation would suggest not.…”
Section: Discussionmentioning
confidence: 99%
“…There is one significant difference between these two viruses which might be responsible for the poorer resistance to CLCuKoV than CLCuKoV-Bu. CLCuKoV-Bu associated with resistance breaking in cotton across Pakistan and northwestern India is the only begomovirus known to lack an intact TrAP-encoding gene (Amrao et al, 2010) that has been found to be important in maintenance of betasatellite (Iqbal et al, 2017). Although one might think that a virus lacking a full TrAP might be impaired, CLCuKoV-Bu is nevertheless infectious (Amrao et al, 2010;Rajagopalan et al, 2012;Zaffalon et al, 2012) and present across a large area of southern Asia (Amrao et al, 2010;Rajagopalan et al, 2012;Zaffalon et al, 2012).…”
Section: Discussionmentioning
confidence: 99%